Analisis Pengaruh Penilaian Kesehatan Bank dan Tax Avoidance pada Kinerja Keuangan Perbankan Konvensional - Septiani, Dwi; Ferdiansyah, Ferdiansyah; Sunarto, Sunarto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara, 2024)
This research aims to examine the influence of bank health assessments and tax avoidance on the financial performance of conventional banks in Indonesia. This research uses data from conventional banks registered with the Financial Services Authority (OJK) with the 2017-2021 financial reporting period. The method used is multiple linear regression analysis with purposive sampling technique. The research results show that Loan to Deposit Ratio (LDR), Operational Costs/Operational Income (BOPO), and Tax Avoidance have a significant effect on bank financial performance. However, LDR did not show a partially significant effect.This research aims to examine the influence of bank health assessments and tax avoidance on the financial performance of conventional banks in Indonesia. This research uses data from conventional banks registered with the Financial Services Authority (OJK) with the 2017-2021 financial reporting period. The method used is multiple linear regression analysis with purposive sampling technique. The research results show that Loan to Deposit Ratio (LDR), Operational Costs/Operational Income (BOPO), and Tax Avoidance have a significant effect on bank financial performance. However, LDR did not show a partially significant effect.